Update on hypertrophic scar treatment (Clinics, 2014)
Scar formation is a consequence of the wound healing process that occurs when body tissues are damaged by a physical injury. Hypertrophic scars and keloids are pathological scars resulting from abnormal responses to trauma and can be itchy and painful, causing serious functional and cosmetic disability. The current review will focus on the definition of hypertrophic scars, distinguishing them from keloids and on the various methods for treating hypertrophic scarring that have been described in the literature, including treatments with clearly proven efficiency and therapies with doubtful benefits. Numerous methods have been described for the treatment of abnormal scars, but to date, the optimal treatment method has not been established. This review will explore the differences between different types of nonsurgical management of hypertrophic scars, focusing on the indications, uses, mechanisms of action, associations and efficacies of the following therapies: silicone, pressure garments, onion extract, intralesional corticoid injections and bleomycin.